Association of Early and Supernormal Vascular Aging categories with cardiovascular disease in the Chinese population - Cao, Qiuyu; Li, Mian; Wang, Tiange; Chen, Yuhong; Dai, Meng; Zhang, Di; Xu, Yu; Xu, Min; Lu, Jieli; Wang, Weiqing; Ning, Guang; Bi, Yufang; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Early Vascular Aging and Supernormal Vascular Aging are two extreme phenotypes of vascular aging, and people in the two categories demonstrate distinct clinical characteristics and cardiovascular prognosis. However, the clinical implication of vascular aging categories in Asian or Chinese population have not been investigated. We aimed to investigate the association between vascular aging categories and cardiovascular events in a Chinese cohort. Methods We explored the association of vascular aging categories with incident cardiovascular disease in a community cohort in Shanghai, China, which included 10375 participants following up for 4.5 years. Vascular age was predicted by a multivariable linear regression model including classical risk factors and brachial-ankle pulse wave velocity. Early and Supernormal vascular aging groups were defined by 10% and 90% percentiles of Δ-age, which was calculated as chronological minus vascular age. Results We found that cardiovascular risk significantly increased in Early (hazard ratio (HR), 1.597[95% CI, 1.043-2.445]) and decreased in Supernormal (HR, 0.729[95%CI, 0.539-0.986]) vascular aging individuals, comparing with normal vascular aging subjects. The associations were independent of Framingham risk score. Early vascular aging individuals also showed elevated risk of total mortality (HR, 2.614 [95%CI, 1.302-5.249]). Further, the associations of vascular aging categories with cardiovascular risk were much stronger in females than in males. Vascular aging categories with different cutoff levels expressed as percentiles (10th, 20th, 25th) of Δ-age showed similar associations with cardiovascular risk. Conclusions In conclusion, the vascular aging categories could identify people with different levels of cardiovascular risk in a Chinese population, particularly in women.